Contemporary Sunni and Ahmadiyya views of Jesus in Ghana in the light of four pre-modern Islamic Sources - Agilinko, Stephen Akpiok-bisa (2017)
This thesis examines contemporary Sunni and Ahmadiyya views of Jesus in Ghana in the light of four pre-modern Islamic sources, namely, the Qur’an, the prophetic tradition (hadith), the exegetical tradition (tafsir) and the pre-modern Muslim anti-Christian polemical tradition. Overall, seventeen treatises comprising eleven Sunni and six Ahmadiyya works are examined in this thesis. Chapter 1 is about the background to the thesis. Chapter 2 explores the person of Jesus from the perspective of four pre-modern sources in Islam. Chapter 3 examines the divinity of Jesus, the Trinity, the Incarnation, the divine sonship of Jesus etc from the standpoint of the contemporary Sunni and Ahmadiyya works. Chapter 4 investigates the death of Jesus from the perspective of the contemporary Sunni and Ahmadiyya works. Chapter 5 summarises the previous four chapters. The first finding of this thesis is that there is substantial theological agreement between the contemporary and pre-modern sources in terms of their representation of Jesus. However, the one fundamental disagreement is that the Ahmadiyya polemicists reject the substitution hypothesis espoused by all the pre-modern sources which posits that Jesus survived death by crucifixion through a miraculous intervention by God resulting in the death of an unnamed substitute. Using Qur’anic, biblical and extra-biblical evidence, the Ahmadiyya polemicists argue that Jesus was crucified, that he swooned on the Cross and was taken down and buried. This theory continues that Jesus came out of the tomb on the third day and travelled to the regions around India where he died many decades later. The second finding is that there are stylistic and methodological differences between the pre-modern sources examined in Chapter 2 and the contemporary sources examined in Chapter 3 and Chapter 4. Chapter 2 shows a philosophically rigorous, theologically sophisticated and rationally robust critique of traditional Christology. By contrast, Chapter 3 and Chapter 4 are largely an aggregation of theological arguments against traditional views of both the divinity of Jesus and his death by crucifixion. Finally, this thesis concludes that the contexts of the pre-modern and contemporary sources, the lack of appreciation of the nuances of traditional Christology by the contemporary polemicists and the needs of the Ghanaian readers may partly account for the differences in the pre-modern and contemporary sources that are examined in thesis.